2005
DOI: 10.1093/brain/awh451
|View full text |Cite
|
Sign up to set email alerts
|

The 9 year cognitive decline before dementia of the Alzheimer type: a prospective population-based study

Abstract: Better knowledge of the preclinical phase of Alzheimer's disease would be an important advance to allow earlier treatment of this ominous disease. This prodromal period was investigated in the Paquid cohort by analysing change in cognitive performances at five time points over a 9 year period. Neuropsychological measures including global cognitive functioning (Mini-Mental State Examination), visuo-spatial memory (Benton Visual Retention Test), verbal fluency (Isaacs Set Test) and abstract thinking (Wechsler Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
290
2
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 375 publications
(323 citation statements)
references
References 38 publications
25
290
2
6
Order By: Relevance
“…Our results extend the findings of Hall et al (2000), who showed that rate of memory decline accelerates years before a diagnosis of AD, to show accelerated memory decline before MCI. The findings are also consistent with those of Amieva et al (2005), who found an accelerated rate of memory decline, in this case on a visuospatial memory recognition test, in highly educated subjects approximately 3 years before a diagnosis AD. Although some studies find that MCI patients at most risk for dementia have only memory impairment, amnestic MCI, we also found accelerated cognitive decline in two nonmemory measures.…”
Section: Discussionsupporting
confidence: 91%
“…Our results extend the findings of Hall et al (2000), who showed that rate of memory decline accelerates years before a diagnosis of AD, to show accelerated memory decline before MCI. The findings are also consistent with those of Amieva et al (2005), who found an accelerated rate of memory decline, in this case on a visuospatial memory recognition test, in highly educated subjects approximately 3 years before a diagnosis AD. Although some studies find that MCI patients at most risk for dementia have only memory impairment, amnestic MCI, we also found accelerated cognitive decline in two nonmemory measures.…”
Section: Discussionsupporting
confidence: 91%
“…Reviews and metaanalyses (Bäckman et al, 2004;Bäckman et al, 2005) of both longitudinal population-based samples and studies on subjects with MCI have evidenced that together with episodic memory deficits, changes in executive functioning and perceptual speed were present in the very early phases. In the same vein, the PAQUID cohort (Amieva et al, 2005) has shown that multiple cognitive functions are affected in the premorbid phase of the AD among which executive …”
Section: Discussionmentioning
confidence: 97%
“…Alzheimer's disease (AD), often considered as the prototype of cortical dementia, impairs both letter and category fluency tasks but semantic fluency would be altered to a greater extent, as suggested by the meta-analysis by Henry et al (2004). The use of semantic fluency proves to be of particular interest not only in the dementia phase but also in the preclinical phase of AD as suggested by a recent prospective population-based study (Amieva et al, 2005). Indeed, the PAQUID study, a French longitudinal population-based study investigated the prodromal period of dementia of the Alzheimer type over a 9-year follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Damage to DNA, lipids and proteins by oxidative free radicals has been implicated in accelerated ageing, degenerative diseases including cancer [3], cognitive decline and impairment, Alzheimer's disease and other dementias [4,5] and Parkinson's disease [6], as well as cardiovascular disease. Population ageing is occurring on a global scale, with faster ageing projected for the coming decades than has occurred in the past [7].…”
Section: Introductionmentioning
confidence: 99%